A framework for decision making of migraine treatment with anti- CGRP monoclonal antibodies: a guide for real-world practice and public policies - Gama, Reinilza Nunes da; Lima, Thaiza Agostini Córdoba de; Dangoni Filho, Iron; Peres, Mario Fernando Prieto (Headache Medicine, 2020)
Anti-CGRP monoclonal antibodies have been developed for migraine preventive treatment. There is evidence of good efficacy and safety of these medications; however, cost is a factor that interferes with the choice of treatment. This paper proposes a framework in order to better assist the decision-making processes on the use of these drugs in developing countries without coverage of health care costs for migraine. The framework was built after reviewing phase II and III studies on episodic and chronic migraine treatment with erenumab, galcanezumab and fremanezumab.